The Implementation of Project-Based Worksheets for Making Taro Tape with Dragon Fruit Peel to Develop Students’ Psychomotor Skills - Ertika, Putrini S.; Subarkah, Cucu Z.; Sukmawardani, Yulia; Sari, Sari (Jurnal Akademika Kimia, 2025)
Developing students’ psychomotor skills is insufficient through theoretical learning in the classroom alone. Still, it must be supported by contextual, practical activities, such as fermenting taro tape with dragon fruit peel, through the application of project-based worksheets. This study aims to analyze students’ ability to complete project-based worksheets and the development of students’ psychomotor skills through testing the characteristics of taro tape. The method employed was a pre-experimental design with a one-shot case study involving tenth-grade students at a senior high school in Bandung City as the research subjects. The assessment instruments included a six-stage project-based worksheet, psychomotor tests covering three characteristics, and product and presentation assessments with eight and six aspects, respectively. Project-based worksheets were implemented in several stages: identifying problems, designing projects, conducting experiments, developing prototypes, evaluating products, and finalizing. The study’s results showed that students’ ability to complete project-based worksheets achieved an average score of 92, categorized as very good. The ability to complete project-based worksheets in the product evaluation stage received the highest score of 100, while the experimentation and prototype development stages received the lowest score of 88. Additionally, the development of students’ psychomotor skills, as measured by the Taro Tape Characteristic Test, showed an average score of 95, categorized as very good. Psychomotor skills in organoleptic tests received the highest score of 100, while the TAT test received the lowest score of 85. Implementing project-based worksheets proved effective in developing students’ psychomotor skills through the stages of project-based learning. These findings underscore the importance of using project-based worksheets as a contextual learning approach that supports chemistry education and fosters active student engagement in developing psychomotor skills.